Pemanfaatan Canva dan YouTube sebagai Media Pembelajaran dalam Pengajaran Bahasa Inggris di MA Hidayatul Insan Palangka Raya - Rizki Hasanah; Zaitun Qamariah (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
English proficiency is a crucial skill in the globalization era, especially in business, communication, and industry sectors, which demand this international language as a competitive advantage. Over the past decade, advancements in Information and Communication Technology (ICT) have significantly impacted English learning, including through online platforms like YouTube and Canva. This study examines the utilization of these two platforms in English teaching at MA Hidayatul Insan Palangka Raya, particularly on the topic "Word Order of Adjective." The methods used include visual presentations with Canva and interactive videos from YouTube. In its implementation, students engaged in dialogues, watched instructional videos, and participated in quizzes as a form of comprehension assessment. The study results indicate that using YouTube and Canva significantly enhances students' participation and learning motivation while reinforcing vocabulary acquisition and comprehension through an interactive approach. Recommendations are provided for the application of these digital media in high school English learning, with suggestions for further research involving long-term impacts and variations in teaching methods across different educational contexts.